Cover Feature: Two β‐Diketiminate Zinc Complexes with 1‐D Chain and Dinuclear Topologies: Synthesis, Structures, and Catalytic Behavior (Eur. J. Inorg. Chem. 20/2022). Issue 20 (22nd June 2022) - Zhang, Liang; Li, Yafei; Wang, Li; Cao, Zhu; Zhang, Qian; Li, Yahong
Abstract : The Cover Feature shows the similarity of [L 1 Zn2 Et2 ]n with the long ribbon of Nezha's hand. Nezha is a Chinese myth hero. One of his magic weapons is the "huntianling", which is an infinite and soft ribbon. This ribbon is very powerful; it could cause chaos for the sun, moon and stars, and chop oceans and cut waves. [L 1 Zn2 Et2 ]n displays a one‐dimensional chain structure. To the best of our knowledge, it is the first β‐diketiminate zinc complex that exhibits an infinite chain topology. It was employed to catalyze the coupling reaction of aryl iodides with B2 Pin2 under milder conditions, with high functional group tolerance and a wide range of substrate scopes. Thus, it resembles the "huntianling" of Nezha both in structure and functionality. More information can be found in the Research Article by Y. Li and co‐workers .